2011
DOI: 10.1007/s10803-011-1265-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Administrative Prevalence of Autism Spectrum Disorders: Contribution of Special Education and Health from 2002–2008

Abstract: This study examined changes in the administrative prevalence of autism spectrum disorders (ASD) in Utah children from 2002 to 2008 by record source (school and health), age (four, six, and eight), and special education classification. Prevalence increased 100% with 1 in 77 children aged eight identified with ASD by 2008. Across study years and age groups rates were higher when health and school data were combined with a greater proportion of cases ascertained from health. The proportion of children with both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…5). A detailed analysis in Utah found that ASD prevalence was higher when estimated based on both health and education data, with a greater proportion of cases ascertained from health records (Pinborough-Zimmerman et al 2012). That analysis may explain part of the large discrepancy between ADDM and IDEA prevalence in Utah shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5). A detailed analysis in Utah found that ASD prevalence was higher when estimated based on both health and education data, with a greater proportion of cases ascertained from health records (Pinborough-Zimmerman et al 2012). That analysis may explain part of the large discrepancy between ADDM and IDEA prevalence in Utah shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The large increase in the number of students with an autism educational classification (Pinborough-Zimmerman et al, 2012), coupled with budgetary concerns in urban school districts, poses a quandary to educators, administrators, and parents. Participants helped elucidate the multiple and varied challenges to providing best practices for ASD treatment in public schools, some of which are consistent with previous research (Kasari and Smith, 2013; Lindstrom, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A similar study design indicates a current ASD prevalence among adults at approximately 1 % (Brugha et al 2011), however studies on adult prevalence are sparse. Furthermore, global ASD prevalence estimates have increased substantially over recent decades (Elsabbagh et al 2012), and over shorter, current time frames (Baird et al 2006;Pinborough-Zimmerman et al 2012;CDC 2014;Ouellette-Kuntz et al 2014). Although increases in the identified prevalence of ASD have been noted at all levels of intellectual ability (Baird et al 2006), they have been more pronounced for those with average or above-average IQ (Elsabbagh et al 2012;Saemundsen et al 2013;CDC 2014).…”
Section: Introductionmentioning
confidence: 99%